Essential Dispositions for Inclusive Educators: An Examination of National Standards and Guiding Principles - Boxtel, Joanne M. Van; Chaney, Megan (Journal of the American Academy of Special Education Professionals, 2024)
Dispositions for inclusive pre-service teachers are recommended by numerous professional organizations and are currently being assessed within teacher preparation programs. Leading professional organizations and agencies have published standards and guiding documents related to essential dispositions for inclusive pre-service and in-service teachers. However, a widely accepted single definition of teacher dispositions does not exist in the literature and there is limited consensus among Institutions of Higher Education (IHEs) regarding the prioritization of dispositions for inclusive pre-service teachers. Assessing essential dispositions remains problematic due to the diverse ways dispositions are operationalized but standards-based approaches are recommended. The researchers examined dispositions defined as behaviors, characteristics, and perceptions within published standards and guiding principles documents of leading professional organizations and agencies to discover consistencies among them. Implications and recommendations for special education teacher preparation programs are discussed.